Hubungan Ukuran Lingkar Lengan Atas Dengan Kejadian Anemia Pada Ibu Hamil Literature Review - Fakhriza, Ilmah; Karnasih, I Gusti Ayu; Aby R, Dian (Jember Maternal and Child Health Journal; Vol 1 No 1 (2024): Jember Maternal and Child Health JournalDO - 10.31290/jmch.v1i1.4939, 2024)
Introduction : Mid Upper Arm Circumference (MUAC) is one indicator to check the nutritional status of pregnant women. Poor nutritional status of pregnant women is a predisposition to anemia in pregnant women in Indonesia. The purpose of this study was to analyze the relationship between upper arm circumference and the incidence of anemia in pregnant women. Methods: The study used is a literature study with the type of Systematic Mapping Study. Articles are taken from databases in the form of Google Schoolar and Researchgate. The population obtained from the database was 25 articles, then screened using the PEOS framework and obtained as many as 5 articles consisting of four national articles and one international article. Results: The five articles showed an average MUAC size <23.5 cm during pregnancy as much as 26.4%, while the average incidence of anemia in pregnant women was 40.3%. The results of the analysis of 5 articles showed that 3 articles showed that there was a relationship between the size of the upper arm circumference and the incidence of anemia in pregnant women with a p-value <?, which means that mothers with LILA <23.5 cm during pregnancy can be at risk of causing anemia in pregnant women. Discussion: The size of MUAC affects nutritional status which has an impact on lack of energy sources so that absorption is impaired, from this incident the mother has an inability to form erythrocytes resulting in hemodilution until the hemoglobin level is <11 g/dl so that the mother is anemic.